2018
DOI: 10.1016/j.solmat.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen induced degradation: A possible mechanism for light- and elevated temperature- induced degradation in n-type silicon

Abstract: In this work, we demonstrate a form of minority carrier degradation on ntype Cz silicon that affects both the bulk and surface related lifetimes. We identify three key behaviors of the degradation mechanism; 1) a firing dependence of degradation extent, 2) the appearance of bulk degradation when wafers are fired in the presence of a diffused emitter and 3) a firing related apparent surface degradation when wafers are fired in the absence of an emitter. We further report a defect capture cross-section ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 59 publications
1
65
0
2
Order By: Relevance
“…Furthermore, recent studies have reported that also anneal made at low-temperature affects the LeTID defect formation [3], [5], [6]. More specifically, it has been shown that a dark anneal (DA) alone can induce degradation and regeneration similar to LeTID and that degradation kinetics and intensity depend on the DA temperature [3], [6], [7], [8], [9], [10]. Additionally, a preliminary study has shown with the experiments made on implied-Voc samples that a long enough anneal at 240-300 °C may have a beneficial effect on the LeTID defect formation under subsequent light soaking [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have reported that also anneal made at low-temperature affects the LeTID defect formation [3], [5], [6]. More specifically, it has been shown that a dark anneal (DA) alone can induce degradation and regeneration similar to LeTID and that degradation kinetics and intensity depend on the DA temperature [3], [6], [7], [8], [9], [10]. Additionally, a preliminary study has shown with the experiments made on implied-Voc samples that a long enough anneal at 240-300 °C may have a beneficial effect on the LeTID defect formation under subsequent light soaking [11].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum temperature is limited to 300 °C in order to have a minimal impact on the junction or contact properties as the anneal times of interest are relatively long. Finally we will study if the degradation and regeneration during DA resemble metal precipitation kinetics, since earlier studies indicate that some metals may still be present in the bulk after the last high temperature step [4], [12], [13], [14], [15] although a strong evidence has been reported for hydrogen playing a crucial role as well [9], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Most part of early discussion in this study is based on the assumption that there is possibly a path of the LeTID defects formation and suppression inside the firing furnace. By assuming that, we are considering a slightly different model for the defect activation from what is usually discussed in some literature [165], [126], [157]. In these recent papers, the LeTID activation and deactivation is considered more related with the hydrogen in-diffusion for the formation of defect reservoirs and hydrogen effusion to drain the reservoir.…”
Section: Source: Authormentioning
confidence: 99%
“…Our results are in accordance whit R. Eberle et.al. [152] and D. Chen et al [165] in terms of resulting LeTID compared with the firing profiles. In Table 12, we compare peak temperature, thermal budget above 600°C, heating and cooling ramp between peak temperature of the profile and 400°C, time above 600°C and if the resulting LeTID is a full degradation curve, a partial degradation curve (minor then the full), or none degradation curve (also almost none degradation).…”
Section: Source: Authormentioning
confidence: 99%
See 1 more Smart Citation